Exercise and executive functioning in older women. (3rd September 2017) - Helmes, Edward; Harris, Steven
ABSTRACT: Research suggests that exercise can slow the rate of decline in cognitive functioning in older adults. The effects of aerobic and resistance exercise on executive functioning was examined in 68 women over 50 years of age. Participants completed the Tower of London and Benton Controlled Oral Word Association tests. Findings indicated that individuals participating in both aerobic and resistance exercises performed significantly better than individuals not participating in exercise. Individuals who were participating in both aerobic and resistance exercises did not perform disproportionately better. Thus the form of exercise appears to be less important than engaging in some form of exercise.